(untitled) (Medico Legal Update, 2019)
Vitamin B12 plays a dynamic role in one carbon metabolism, which is essential for the general healthy pregnancy and predominantly for fetal growth. Another parameter is maternal glucose during pregnancy. For the transport of the glucose across the placenta, insulin resistance is change for the normal development of the fetus. This study included 30 pregnant women enrolled at Al-Karkh Materuity hospital in January to May 2019. The pregnant women with 23rd to 25th gestational week were included in the present study. Fasting blood was collected form cases (either showed vitamin B12 deficiency or high serum glucose) and healthy participants after obtaining informed consent. The parameters like child birth weight, type of delivery and duration of pregnancy was recorded. The vitamin B12 content was significantly lower (222.43±48.41pg/ml) in the B12 deficient group as compared to healthy control (492.71±52.81 pg/ml). It was observed that the women with B12 deficiency lead to the premature delivery. The fetus birth weight is negatively correlated with the presence of vitamin B12 deficiency. Compared to the healthy control, women with high serum glucose showed significant (p?0.0001) increased in the fetus weight, which may be one of the reason for C-section delivery. About 87.32% GDM women undergone C-section delivery, while only 12.68% normal delivery occurs. Most of the normal child delivery was found in the B12 deficient women and maximum normal child delivery rate was in the healthy control. The fetus birth weight is positively correlated with the presence of increased serum glucose leves of the mother. It was positively correlated with the pregnancy complications such as premature birth, increased in fetus weight etc. For anaemic condition in the mother, vitamin B12 deficiency can be one of the key factor and it should be monitored before planning of pregnancy.